The Formation and Development of Theatrical Art in the Fergana Valley: Analysis of Historical Stages and Cultural Traditions - Abdurahimov, Javlonbek (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article examines the formation and development of theatrical art in the Fergana Valley, one of the most culturally rich regions of Uzbekistan. The research traces the evolution of theater from early folk performances, musical storytelling, and traditional dramatic expressions to the establishment of professional theaters during the Soviet period and their transformation in the years of independence. The study emphasizes the interplay between national cultural heritage and modern stage aesthetics, as well as the impact of social, political, and ideological factors on the artistic process. The article concludes that the Fergana Valley has played a decisive role in shaping the regional identity of Uzbek theater, serving as a bridge between traditional values and contemporary forms of artistic expression.